Metal hydrides for concentrating solar thermal power energy storage - Sheppard, D. A.; Paskevicius, M.; Humphries, T. D.; Felderhoff, M.; Capurso, G.; Bellosta von Colbe, J.; Dornheim, M.; Klassen, T.; Ward, P. A.; Teprovich, J. A.; Corgnale, C.; Zidan, R.; et al. (Springer Verlag, 2016)
The development of alternative methods for thermal energy storage is important for improving the efficiency and decreasing the cost for Concentrating Solar-thermal Power (CSP). We focus on the underlying technology that allows metal hydrides to function as Thermal Energy Storage (TES) systems and highlight the current state-of-the-art materials that can operate at temperatures as low as room-temperature and as high as 1100 oC. The potential of metal hydrides for thermal storage is explored while current knowledge gaps about hydride properties, such as hydride thermodynamics, intrinsic kinetics and cyclic stability, are identified. The engineering challenges associated with utilising metal hydrides for high-temperature thermal energy storage are also addressed.